Effectiveness of Mental Health Literacy in Group Guidance Against Mental Health Stigma - Isma Isma; Ikhlas Rasido; Dhevy Puswiartika; Hasan Hasan (MASI Mandiri Edukasi, 2026)
Low mental health literacy contributes to high mental health stigma among students. This study aims to examine the effectiveness of mental health literacy-based group counselling services in reducing mental health stigma among students at MAN 1 Kota Palu. The study uses a quantitative approach with a pretest–posttest control group quasi-experimental design. The sample comprised 21 students, divided into an experimental and a control group. The experimental group received six sessions of mental health literacy-based group counselling services, while the control group did not receive any treatment. The research instruments used were the Mental Health Literacy Questionnaire–Short Version Adult (MHLq-SVa) and the Mental Health Stigma Scale. Data analysis was performed using the Wilcoxon and Mann–Whitney tests. The results showed a significant increase in mental health literacy and a decrease in mental health stigma in the experimental group (p < 0.05), as well as a significant difference between the experimental and control groups (p = 0.000). These findings indicate that mental health literacy-based group counselling is an effective psychosocial intervention in school settings.